Probing the energy conversion process in piezoelectric-driven electrochemical self-charging supercapacitor power cell using piezoelectrochemical spectroscopy - Karthikeyan Krishnamoorthy (Nature Portfolio, 2020)
Devices that are capable of energy harvesting and storage are attractive for meeting daily energy demands, however they are limited by efficiency. Here the authors fabricate a siloxene-based self-charging supercapacitor power cell and probe the piezoelectrochemical effect involved in the charging process.